Cell free fetal DNA testing in maternal blood of Romanian pregnant women - Viorica E Radoi; Camil L Bohiltea; Roxana E Bohiltea; Dragos N Albu (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: The discovery of circulating fetal DNA in maternal blood led to the discovery of new strategies to perform noninvasive testing for prenatal diagnosis. Objective: The purpose of the study was to detect fetal aneuploidy at chromosomes 13, 18, 21, X, and Y by analysis of fetal cell-free DNA from maternal blood, without endangering pregnancy. Materials and Methods: This retrospective study has been performed in Bucharest at Medlife Maternal and Fetal Medicine Department between 2013-2014. In total 201 women were offered noninvasive prenatal test. Maternal plasma samples were collected from women at greater than 9 weeks of gestation after informed consent and genetics counseling. Results: From 201 patients; 28 (13.93%) had screening test with high risk for trisomy 21, 116 (57.71%) had advanced maternal age, 1 (0.49%) had second trimester ultrasound markers and the remaining 56 patients (27.86%) performed the test on request. Of those patients, 189 (94.02%) had a "low risk" result (<1/10,000). Of those who had a low risk result, 2 continued on to have amniocentesis with normal results.Five patients (2.48%) received "high risk" results (>99% risk) all for trisomy 21 (T21). T21 was confirmed by amniocentesis in 1 patient and the other 4 patients declined confirmation. The 7 remaining patients (3.48%) had a low fetal fraction of DNA. Conclusion: It is probably that prenatal diagnosis using fetal DNA in maternal blood would play an increasingly role in the future practice of prenatal testing because of high accuracy.